Experimental study on mechanical properties of saucer tray used in mine - Jinglong Jia; Fenghai Yu; Yunliang Tan; Yubao Zhang; Xingyin Ma (E3S Web of Conferences, 2021)
This paper takes the saucer tray as the research object, carries on the unidirectional compression test to it in the room, through the monitoring of the deformation characteristics of the saucer tray, analyzes the deformation characteristics of the saucer tray. According to its deformation characteristics, the saucer tray is divided into deformation areas. A static strain gauge was used to monitor the strain at the measuring point on the surface of the tray and the stress distribution on the exposed surface of the tray was studied. It is intended to infer the force of the disk-shaped tray through its deformation degree, which provides a certain theoretical basis and practical guiding significance for the research of disk-shaped tray.